Percy Jackson. Sea of monsters [videorecording (DVD)] - Freudenthal, Thor; Lerman, Logan, 1992-; Daddario, Alexandra, 1986-; Jackson, Brandon T., 1984-; Abel, Jake, 1987-; Smith, Douglas, 1985-; Tucci, Stanley; Fillion, Nathan, 1971-; Riordan, Rick
Based on the publishing phenomenon, Percy Jackson and other young demigods continue to fight, but this time in the sea, to fulfill their destinies. To save their world, Percy and his friends must find the fabled and magical Golden Fleece. Embarking on a treacherous odyssey into the uncharted waters of the Sea of Monsters (known to humans as the Bermuda Triangle), they battle terrifying creatures, an army of zombies, and the ultimate Evil.